2021
DOI: 10.1038/s41598-021-03098-x
|View full text |Cite
|
Sign up to set email alerts
|

Validation of reference genes for quantitative real-time PCR in chemical exposed and at different age’s brackish water flea Diaphanosoma celebensis

Abstract: Real-time quantitative reverse transcription polymerase chain reaction (qRT-PCR), a primary approach for evaluating gene expression, requires an appropriate normalization strategy to confirm relative gene expression levels by comparison, and rule out variations that might occur in analytical procedures. The best option is to use a reference gene whose expression level is stable across various experimental conditions to compare the mRNA levels of a target gene. However, there is limited information on how the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 58 publications
(51 reference statements)
0
2
0
Order By: Relevance
“…In the last decades, the genes known as housekeeping genes were broadly used as internal controls for the normalization of RNA levels for Northern blotting, RNAse protection and RT-qPCR analyses, because it was assumed that these genes are constitutively expressed and regulated, but no studies indeed evaluated the stability of expression of these genes under various experimental conditions 7,14 . Moreover, it has been shown that the expression levels of these housekeeping genes vary depending on the conditions and tissues in which are expressed [15][16][17][18][19] . Therefore, it is hard to select a perfect RG that would be consistently expressed in all tissues and cell types without being in uenced by internal or external factors.…”
Section: Discussionmentioning
confidence: 99%
“…In the last decades, the genes known as housekeeping genes were broadly used as internal controls for the normalization of RNA levels for Northern blotting, RNAse protection and RT-qPCR analyses, because it was assumed that these genes are constitutively expressed and regulated, but no studies indeed evaluated the stability of expression of these genes under various experimental conditions 7,14 . Moreover, it has been shown that the expression levels of these housekeeping genes vary depending on the conditions and tissues in which are expressed [15][16][17][18][19] . Therefore, it is hard to select a perfect RG that would be consistently expressed in all tissues and cell types without being in uenced by internal or external factors.…”
Section: Discussionmentioning
confidence: 99%
“…In the last decades, genes known as housekeeping genes were broadly used as internal controls for the normalization of RNA levels for Northern blotting, RNAse protection, and RT-qPCR analyses because it was assumed these genes are constitutively expressed and regulated, but no studies have evaluated the stability of expression of these genes under various experimental conditions 11 , 23 . Moreover, the expression levels of these housekeeping genes vary depending on the conditions and tissues expressed 24 28 . Therefore, it is difficult to select a perfect RG that would be consistently expressed in all tissues and cell types without being influenced by internal or external factors.…”
Section: Discussionmentioning
confidence: 99%